COMPETENCY-BASED ENGLISH TEACHING IN BENIN: MYTH OR REALITY? - Koussouhon, Léonard; IWIKOTAN, K. ETIENNE (My University, 2015)
In Benin, the implementation of a competency-based curricula reform in secondary education began in 2001. The objective of this study is to find out whether the English curricula are truly competency-based. To that effect, some members of the curricula development team were interviewed and the curricula as well the textbooks of all four grade levels covered by the study were reviewed. The findings of the study revealed that the procedures followed to develop the curricula are not consistent with available frameworks for developing a competencybased curriculum (Weddel, 2006; Mrowicki, 1986). Not only are the selected competencies too broad and unspecific but the assessment criteria were not developed before the actual implementation of the curricula. In addition, individualization of instruction, which is one of the key features of the approach, is difficult to apply given the large number of students in Beninese secondary school classrooms. Finally, most of the materials in the textbooks are contrived and as such they are not likely to prepare students for real-life situations. All these shortfalls are certainly due to the fact that the curricula development team members interviewed did not seem to be very conversant with the competency-based approach. All in all, the English curricula currently implemented in Beninese secondary schools are far from being competency-based.
Keywords: Curriculum; Competency-based approach; Secondary; Education